Gustave Doré and the modern biblical imagination - Schaefer, Sarah (Oxford University Press USA - OSO, 2021)
Gustave Doré and the Modern Biblical Imagination explores the role of biblical imagery in modernity, an era that has often been defined through a process of secularization. It does so through the lens of Gustave Doré (1832-83), whose work is among the most reproduced and adapted scriptural imagery in the history of Judeo-Christianity. The book argues that Doré's biblical imagery negotiated the challenges of visualizing the Bible for modern audiences in both sacred and secular contexts. A set of texts whose veracity and authority were under unprecedented scrutiny in this period, the Bible was at the center of a range of historical, theological, and cultural debates. Gustave Doré is at the nexus of these narratives, as his work established the most pervasive visual language for biblical imagery in the past two and a half centuries, and constitutes the means by which the Bible has persistently been translated visually.